Effect of eccentric overload through isoinertial technology in basketball players - Cabanillas, R.; Serna, J.; Muñoz-Arroyave, V.; Echeverri Ramos, J. A. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2020)
The present study investigated the effect of eccentric overload on professional basketball players. Participants were 8 players aged 18-25 years who play in a Leb Oro League team. There was an 8 week training cycle with 1 weekly session of half squats. The control group performed training following a traditional methodology -using free weights- whereas the experimental group used inertial technology, that is, the ProSquat machine from Proinertial®. Both vertical jump and 30-meter sprint were assessed before and after intervention. The following conclusions were reached: a) strength training with vertical vector improves the 30-meter sprint test and also the vertical jump; b) training program that affects the eccentric overload of the movement results in more improvements than traditional training with the same duration; c) training in the vertical vector also has an impact on the way force is manifested in the horizontal vector, showing improvements in the 30-meter sprint.